Pengaruh Hafalan Al-Qur’an Terhadap Minat Belajar Matematika di Pondok Penghafal Alqur’an - Nasution, Novia Ramadani; Hasibuan, Eka Khairani (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2023)
This study aims to determine whether there is an influence between memorizing the Koran and interest in learning mathematics. The researcher found that the higher the student’s memorization level greatly influenced their interest in learning mathematics, and the results obtained were also getting better. The method used in this research is a quantitative method. The instruments used in this study were questionnaires and mathematical questions about geometric shapes. The instrument has previously been validated by researchers and has been tested through the SPSS 20 program and has been proven valid. Based on the results of the normality test, it is known that the significance value is more than 0.05, so the residual value is normally distributed. The subjects of this study were class VIII students of the Zawiyatul Huffazh Al-Qur'an Memorization Board. The results showed that there was an influence between memorizing the Koran on students' learning interest.